ANALYSIS OF THE INNOVATIVE MICROTEACHING LEARNING MODEL IN ENHANCING TPACK COMPETENCE OF PROSPECTIVE TEACHERS OF MADRASAH IBTIDAIYAH - Isro’iyah, Isro’iyah; Nisak, Nur Maslikhatun; Supriyanto, Eko Budi; Astuti, Ruli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the effectiveness of an innovative microteaching model in enhancing the TPACK (Technological, Pedagogical, and Content Knowledge) competence of prospective teachers of Madrasah Ibtidaiyah (MI) at Muhammadiyah University Sidoarjo. Despite the crucial role of technology in contemporary education, MI prospective teachers often encounter challenges integrating TPACK into their teaching practices. Therefore, an innovative microteaching model is adopted as an approach to address these obstacles. The research employs a qualitative approach with a case study design, collecting data through observation, interviews, and documentation. The results reveal that MI prospective teachers face obstacles such as limited knowledge of technology and difficulties in designing effective technology-integrated lessons. The innovative microteaching model, involving steps like identifying TPACK needs, instructional design, microteaching implementation, and reflection, proves effective in enhancing TPACK competence. MI prospective teachers experience improvements in knowledge, the development of skills in designing technology-integrated lessons, and enhanced teaching abilities. Practical recommendations from this research emphasize the integration of the innovative microteaching model into the curriculum and training programs for MI prospective teachers. The importance of technological infrastructure development in MI is also underscored. With the implementation of this model, it is expected that MI prospective teachers can enhance their TPACK competence and provide quality learning experiences to MI students in the digital era. This research contributes significantly to the development of MI education with a focus on the use of technology in learning.